Reproductive Medicine and Biology - Sugino, Norihiro; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer.)
Reproductive Medicine and Biology (RMB) is the official English journal of the Japan Society for Reproductive Medicine, the Japan Society of Fertilization and Implantation, the Japan Society of Andrology, and the Asian Society of Endometriosis and Adenomyosis, and publishes original research articles that report new findings or concepts in all aspects of reproductive phenomena in all kinds of mammals. Papers in any of the following fields will be considered: andrology, endocrinology, oncology, immunology, genetics, function of gonads and genital tracts, erectile dysfunction, gametogenesis, function of accessory sex organs, fertilization, embryogenesis, embryo manipulation, pregnancy, implantation, ontogenesis, infectious disease, contraception, infertility treatment, surgery, ethics and social issues, at the biological, biochemical, biophysical, molecular biological, analytically morphological and clinical levels. Reports on techniques applicable to the above field are also considered. Original Articles, Research Notes and Case Reports will be accepted, but not preliminary reports.
Keywords: Gynecology; Reproductive medicine; Urology; Reproductive Medicine; Gynecology; Urology